RELATIONSHIP BETWEEN ALACTIC ANAEROBIC POWER TESTS: SEARCHING ALTERNATIVE FOR THE PHYSICAL EVALUATION (Fiep Bulletin - online, 2014)
The anaerobic power is an important parameter for the evaluation of the physical capacity of the athlete. The Wingate Anaerobic Test is the gold-standard for the evaluation of this capacity, but many times its application is complex and expensive. Being thus, the objective of this study was to analyze if squat jump (SJ), countermovement jump (CMJ) and sprint of race in 10 m (V10) and 40 m (V40) evaluate the referring parameters to the developed alatic anaerobic power. Ten volunteers (23±8 years, 64±21 kg, 161±47 cm), had carried through the tests of Wingate, 40 race of 10 and m, squat jump (SJ) and countermovement jump (CMJ). The correlations between the data of reached relative maximum power (PMáxRel), time to reach the maximum power (TPMáx), sprint of race (V10 and V40) and height of the jumps had been analyzed. This study showed that the TPMáx did not present significant correlation with no 0 variable. The PmáxRel had greater correlation with the sprint of the V40 (r=0.962) that with the one of the V10 (r=0.832), and greater correlation with the performance in the CMJ (r=0.944) that in the SJ (r=0.920). The correlation enters the values of the jumps and of the race it showed that both the jumps had had greater correlation with the V40 (SJ=0,905 and CMJ=0,945) that with the V10 (SJ=0,826 and CMJ=0,870). Moreover, both sprint values (TV10 and TV40) had presented greater correlation with the CMJ (V10=0,870 and V40=0,945) that with the SJ (V10=0,826 and V40=0,905). One concludes that all the applied tests, V10, V40, SJ and CMJ, are efficient for the evaluation of the alatic anaerobic power.
Keywords: anaerobic power; sprint test; jump